DEVELOPMENT OF TIMBER PROCESSING COMPLEX OF THE RUSSIAN FEDERATION AGAINST THE BACKGROUND OF UNIVERSAL TRENDS - P. Chomaev (Вестник университета)
Object of research in this article is the timber processing complex, that plays an important role in structure of Russia’ industrial production. A research objective is the assessment of results of development of timber processing complex in our country in comparison with universal tendencies. Results of a research showed serious lag of industry in comparison with forest complexes of foreign countries. Questions of formation and development of timber industry clusters, innovative and export-oriented woodworking industry are especially relevant in our country. In the article the analysis of the main problems, opportunities and directions of the industry’s development in the conditions of integration of Russia into the world market is carried out.